High Fat High Sugar Diet Reduces Voluntary Wheel Running in Mice Independent of Sex Hormone Involvement - Vellers, Heather L.; Letsinger, Ayland C.; Walker, Nicholas R.; Granados, Jorge Z.; Lightfoot, J. Timothy (Frontiers in Physiology, 2017)
Introduction: Indirect results in humans suggest that chronic overfeeding decreases physical activity with few suggestions regarding what mechanism(s) may link overfeeding and decreased activity. The primary sex hormones are known regulators of activity and there are reports that chronic overfeeding alters sex hormone levels. The purpose of this study was to determine if chronic overfeeding altered wheel running through altered sex hormone levels. Materials and Methods: C57BL/6J mice were bred and the offspring were weaned at three-weeks of age and randomly assigned to either a control (CFD) or high fat/high sugar (HFHS) diet for 9-11 weeks depending on activity analysis. Nutritional intake, body composition, sex hormone levels, and three-day and two-week wheel-running activity were measured. Additionally, groups of HFHS animals were supplemented with testosterone (males) and 17β-estradiol (females) to determine if sex hormone augmentation altered diet-induced changes in activity. Results: 117 offspring (56♂, 61♀) were analyzed. The HFHS mice consumed significantly more calories per day than CFD mice (male: p<0.0001; female: p<0.0001) and had significantly higher body fat (male: p<0.0001; female: p<0.0001). The HFHS diet did not reduce sex hormone levels, but did significantly reduce acute running-wheel distance in male (p=0.05, 70±28%) and female mice (p=0.02, 57±26%). In animals that received hormone supplementation, there was no significant effect on activity levels. Two-weeks of wheel access was not sufficient to alter HFHS-induced reductions in activity or increases in body fat. Conclusion: Chronic overfeeding reduces wheel running, but is independent of the primary sex hormones.